PENGARUH PENGUNGKAPAN LAPORAN BERKELANJUTAN TERHADAP MANAJEMEN LABA - Lusiana Puspita Sari; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2019)
The aims of this research to asses the effects of disclosure of sustainability reports on earnings management. Disclosure of sustainability reports as an independent variable measured by GRI G4. Earnings management as a dependent variable and it is measured by discretionary accruals of the modified Jones model. The selection of the research sample was carried out by using a purposive sampling method on all Indonesian non-financial companies that published sustainability reports. The number of final samples obtained was 54 consisting of 18 companies in the period 2015 to 2017. The analysis techinique in research using the panel data regression. Overall, the results of the research indicate that disclosure of sustainability reports has a negative and significant effect. So, the sustainability report disclosure by the company can reduce the existence of earnings management. In this research also involves several control variables such as the level of profitability, leverage, the board of commissaris size and the audit committee size. Leverage, the board of commissaris size, and audit committee size have a negative and insignificant influence. While the profitability has positive and insignificant influence.